0404 Surveillance of occupational eye injury through emergency services: two-year experiences in a medical centre of taiwan. (21st August 2017) - Weng, Ting-Chia; Hsu, I-Lin; Chuang, Chia-Chang; Wang, Jung-Der; Guo, How-Ran; Kuo, Yau-Chang
Abstract : Ocular trauma in the workplace is a worldwide cause of visual morbidity, but is largely preventable. We established a pilot surveillance system of occupational eye injuries at emergency service of National Cheng Kung University Hospital (NCKUH) from Feb 2015 to Feb 2017. During the study period, 114 events of occupational eye injuries were collected with 22 patients further hospitalised. Among them, 3 cases of severe ocular trauma were accompanied with other injuries resulting in an Injury Severity Score of more than 16. Foreign body injury (28%, n=32) and chemical burn (21%, n=24) were the most frequent eye injuries. Notably, 12 cases (10.5%) eyeball rupture were identified. The total medical costs charged through the NCKUH were about 66, 000 USD for these ocular trauma patients, counting emergency and hospitalisation fees within 90 days after the first encounter. Eyeball ruptures accounted for 57.5% of the total medical charges. Only about 18% of occupational ocular trauma cases were reported to the National Labour Insurance and would usually be compensated. This study highlights the urgent needs of comprehensive compulsory regulations of recognition and report, compensation, and prevention and control of occupational eye injuries in the workplace of Taiwan.